Metal-catalysis in industrial organic processes - Chiusoli, Gian Paolo; Maitlis, Peter M., 1933- (Royal Society of Chemistry (Great Britain), 2006)
Catalysis underpins most modern industrial organic processes. It has become an essential tool in creating a 'greener' chemical industry by replacing more traditional stoichiometric reactions, which have high energy consumption and high waste production, with mild processes which increasingly resemble Nature's enzymes. Metal-Catalysis in Industrial Organic Processes considers the major areas of the field and discusses the logic of using catalysis in industrial processes. The book provides information on oxidation, hydrogenation, carbonylation, C-C bond formation, metathesis and polymerization processes, as well as on the mechanisms involved. In addition two appendices offer a concise treatment of homogeneous and heterogenous catalysis. Numerous exercises referring to problems of catalytic processes, and research perspectives complete the book. This definitive reference source, written by practising experts in the field, provides detailed and up-to-date information on key aspects of metal catalysis.